Trade and fisheries: Key issues for the World Trade Organization - Frank Asche; Martin D. Smith (World Trade Organization (WTO), 2010)
Fisheries are common-pool resources, and many of world's fisheries are overexploited. At the same time, capture fisheries and aquaculture operations can impinge on public goods provided by marine ecosystems such as marine biodiversity and unique habitat. The common-pool and public goods dimensions of the marine environment justify regulation, but the issues frequently transcend national boundaries. Individual countries have few alternatives to protect the marine environment beyond their own jurisdictions. The international nature of marine conservation thus provides an incentive for countries to use trade policy as an indirect means to protect the marine environment. Because a large share of the available seafood is being traded, trade restrictions can potentially lead to better resource protection and better fishing practices.
Keywords: 330; Fischereiressourcen; Internationale Handelspolitik; WTO-Regeln